2004
DOI: 10.1111/j.1468-0262.2004.00554.x
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Testing of Cointegrating Relationships

Abstract: In this paper we investigate methods for testing the existence of a cointegration relationship among the components of a nonstationary fractionally integrated (NFI) vector time series. Our framework generalizes previous studies restricted to unit root integrated processes and permits simultaneous analysis of spurious and cointegrated NFI vectors. We propose a modified F-statistic, based on a particular studentization, which converges weakly under both hypotheses, despite the fact that OLS estimates are only co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 47 publications
(50 reference statements)
1
71
1
Order By: Relevance
“…If r > 1 and the observables and cointegrating residuals are purely nonstationary, Marmol and Velasco (2005) showed that, in contrast to the standard C(1, 1) case (see Wooldrige (1991), Johansen (2002), the OLS estimate of the cointegrating vector (1, Γ ) does not provide a consistent estimate of a suitable linear combination of the cointegrating relations, though remains bounded in probability. Despite of that, in our setting of common error memory of cointegrating residuals, it was shown that the OLS residualsê t still approximate an I(1 − b) process as in the single equation set-up.…”
Section: Testing the Cointegration Rankmentioning
confidence: 99%
See 3 more Smart Citations
“…If r > 1 and the observables and cointegrating residuals are purely nonstationary, Marmol and Velasco (2005) showed that, in contrast to the standard C(1, 1) case (see Wooldrige (1991), Johansen (2002), the OLS estimate of the cointegrating vector (1, Γ ) does not provide a consistent estimate of a suitable linear combination of the cointegrating relations, though remains bounded in probability. Despite of that, in our setting of common error memory of cointegrating residuals, it was shown that the OLS residualsê t still approximate an I(1 − b) process as in the single equation set-up.…”
Section: Testing the Cointegration Rankmentioning
confidence: 99%
“…Despite of that, in our setting of common error memory of cointegrating residuals, it was shown that the OLS residualsê t still approximate an I(1 − b) process as in the single equation set-up. See also Marmol and Velasco (2004) for a discussion.…”
Section: Testing the Cointegration Rankmentioning
confidence: 99%
See 2 more Smart Citations
“…Velasco (2003) considers semiparametric consistent estimation of the memory parameters of a nonstationary fractionally cointegrated vector time series. Marmol and Velasco (2004) propose tests of the null of cointegration, without information on the degree of integration, based on Wald statistics for OLS coe¢ cients. Hualde and Velasco (2008) employ GLS-type of estimator as in Robinson and Hualde (2003) and obtain a chi-squared distribution for the Wald test under the null of no cointegration.…”
Section: Introductionmentioning
confidence: 99%